Pressure and volume controlled mechanical ventilation in anaesthetized pregnant sheep. (October 2014) - Davis, J; Musk, GC
Optimal mechanical ventilation of the pregnant ewe during anaesthesia is of vital importance for maintaining fetal viability. This study aimed to compare peak inspiratory pressure (PIP), oxygenation and cardiovascular parameters with pressure-control (PCV) or volume-control (VCV) mechanical ventilation of anaesthetized pregnant sheep. Twenty ewes at 110 days gestation underwent general anaesthesia in dorsal recumbency for fetal surgery in a research setting. All the sheep were mechanically ventilated; one group with PCV ( n = 10) and another with VCV ( n = 10) to maintain normocapnia. PIP, direct arterial blood pressure, heart rate, arterial pH and arterial oxygen tension were recorded. PIP was lower in the PCV group ( P < 0.001). Arterial oxygen tension was higher in the PCV group ( P = 0.013). Mean and diastolic pressures were lower in the PCV group ( P = 0.029 and P = 0.047, respectively). Both VCV and PCV provide adequate oxygenation of pregnant sheep anaesthetized in dorsal recumbency, though PCV may provide superior oxygenation at a lower PIP.